Obese children and adolescents need increased gastric volumes in order to perceive satiety. (29th July 2014) - Mack, Isabelle; Sauer, Helene; Weimer, Katja; Dammann, Dirk; Zipfel, Stephan; Enck, Paul; Teufel, Martin
<x xml:space="preserve">Abstract</x> Objective In order to develop effective weight management strategies, it is important to identify factors that influence energy intake. Portion size has been discussed as one such factor. To date, most studies focusing on the relationship between portion size, energy intake, and weight have analyzed questionnaire data and 24‐h records. In this study, we assessed the onset of satiety using the water‐load test in normal‐weight and obese children and adolescents. Methods 60 obese and 27 normal‐weight children and adolescents aged between 9 and 17 years participated in the water load test which involved drinking water for 3 min or until feeling full. The amount of water consumed was recorded. Results Obese children and adolescents drank 20% more water until the onset of satiety when compared with normal‐weight participants (478 ± 222 ml vs. 385 ± 115 ml, P < 0.05). Conclusions Obese children and adolescents need to ingest greater volumes to feel full which may predispose toward the consumption of larger portion sizes. This may easily lead to overeating if predominantly energy‐dense foods are consumed. A reduction in energy‐dense foods in the diet of obese children and adolescents appears to be a necessary strategy for managing body weight.